An investigation of riskiness in South and Eastern European markets. (15th December 2006) - Kalyvas, Lampros; Sfetsos, Athanasios; Siriopoulos, Costas; Georgopoulos, Antonios
The present study adds evidence, from three former emerging and currently transition countries along with two EU member countries of South and Eastern Europe, relevant to the market risk their stock exchanges possess under the same global financial environment. In order to assess market risk, we use four Value-at-Risk methodologies, namely, Historical Simulation (HS), Conditional Historical Simulation (CHS), Extreme Value Theory (EVT) and Conditional Extreme Value Theory (CEVT). Hungary exhibits higher risk under extreme conditions indicating that its market is much more vulnerable than all other markets under study.